(untitled) (Journal of the College of Education for Women, 2019)
That writing about the Iraqi Museum, within this context that comes second only to the Egyptian Museum , in terms of the establishment , not least his affair in terms of the historical value of the effects that represent the civilization of Iraq and his history of the old , which stretches for thousands of years until it became a landmark and cultural landmarks the city of Baghdad salient .The motive for the study of the subject of the Iraqi Museum upbringing and development until 1963 , we did not find a study documented by the independent research except for studies that are specialized to study the ancient history of Iraq and its effects was the outcome of efforts exploration missions archaeological that stretched across decades of time, large amounts of the effects that they had extracted from the arms of the earth and that deposited in the Iraqi Museum, the subject of this research .